99.5k views
3 votes
Approximate the solution to this system of equations. y = –2x + 6 y = 4x – 1

User Debhere
by
5.1k points

1 Answer

4 votes

Answer:

x = 1
(1)/(6), y = 3
(2)/(3)

Explanation:

y = -2x + 6 --- Equation 1

y = 4x - 1 --- Equation 2

Since both (-2x + 6) and (4x - 1) have the same total, y, they are equal.

-2x + 6 = 4x - 1

Isolate the like terms.

6 + 1 = 4x + 2x

Evaluate like terms.

6x = 7

Find x.

x =
(7)/(6)

x = 1
(1)/(6)

Substitute x =
(7)/(6) into Equation 2:

y = 4x - 1

y = 4(
(7)/(6)) - 1

= 4
(2)/(3) - 1

y = 3
(2)/(3)

User Ormaaj
by
5.5k points